Manufacturing concentrates Alholucramih for use in increasing the efficiency of solar cell - Baghdad Science Journal (مجلة بغداد للعلوم)
A new way to Systems concentrates have been clarified and that allows a concentration high and analysis to automatically wavelengths of the spectrum of this system analyst of the spectrum and the center is built on Holucram Nafez gives less absorbency with efficient diffraction high when the wavelength (900 nm), which will be useful for Khallaya solar